Review of Active Noise Control Technology of Railway Vehicle - LUO Zhuhui; LI Tao; HE Caichun; ZHANG Yaxin; ZHOU Xisheng; LI Zhuang (机车电传动)
Interior noise of railway vehicle especially high-speed train increases with vehicle’s speed increasing. Compared with passive noise control such as sound insulation and absorption, active noise control (ANC) has many advantages such as lightweight and effective for attenuating with low frequency noise. Active noise control technology and noise source characteristics of railway vehicle was introduced briefly. Present research status of ANC technology for decreasing railway vehicle noise at home and abroad was reviewed. A brief analysis about arrangement strategy of secondly sound resource and error sensors and FXLMS control algorithm was provided. Development trend about ANC technology for decreasing interior noise of railway vehicle was preliminary discussed.